2017
DOI: 10.1177/1687814017695757
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of large-scale micro-structures by two-photon polymerization with a long-stroke precision stage

Abstract: This article demonstrates the fabrication of large-scale micro-structures by two-photon polymerization with an integrated long-stroke precision stage. We first design a three-axial stage that combines a piezoelectric transducer stage and a stepper-motor stage, and we apply gain-scheduling and robust control with a feedforward compensator to achieve nano-positioning within a travel range of 10 cm. We then integrate the precision stage with a two-photon polymerization module to manufacture large-scale micro-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Among 3D printing technologies, it has been demonstrated that multiple photon polymerization (MPP) has the highest resolution in comparison to other printing techniques (around 100 nm or less) [21,69,71]. Research in resolution improvement of mesoscale lenses fabricated by MPP is limited to process improvements by controlling parameters [72,73] and developing new resins [74][75][76], new systems [16,64,[77][78][79], or laser scanning algorithms [80,81].…”
Section: Multiphoton Stereolithographymentioning
confidence: 99%
“…Among 3D printing technologies, it has been demonstrated that multiple photon polymerization (MPP) has the highest resolution in comparison to other printing techniques (around 100 nm or less) [21,69,71]. Research in resolution improvement of mesoscale lenses fabricated by MPP is limited to process improvements by controlling parameters [72,73] and developing new resins [74][75][76], new systems [16,64,[77][78][79], or laser scanning algorithms [80,81].…”
Section: Multiphoton Stereolithographymentioning
confidence: 99%
“…The dual-stage structure had been widely utilized in precision positioning stages, where the lower stage provides the large stroke, yet course positioning, and the upper stage provides the short stroke, yet precision positioning. 24 In our case, the dual-stage structure is designed for fast response rather than precision positioning. The lower stage is composed of a tracked robot, so the motion range is not confined like other systems composed of a positioning stage.…”
Section: Introductionmentioning
confidence: 99%